Strukturierte Karrierewege in der Universitätsmedizin - Thimme, Robert; Pahl, Heike L.; Werner, Karin; Nagel, Irene E.; Bruckner-Tuderman, Leena (DMW - Deutsche Medizinische Wochenschrift, 2019)
Scientifically active medical doctors are required for successful translation of novel basic findings into the clinic. However, there is an increasing tendency of young medical doctors to primarily follow a more clinically and not scientifically orientated career pathway. Therefore, the establishment of novel career education structures and career perspectives in university medicine are important to stop this development. Here, we will discuss the current situation and ongoing attempts to design novel structural programs that allow a better combination of clinical and scientific work by highlighting also current developments at the Faculty of Medicine at the University of Freiburg.
Keywords: structured career pathway; university medicine; clinician scientist program; doctoral thesis